Cracker from Kilka - Shojaei, Amir H. (Fishery Technology, 2025)
A study was undertaken for the preparation of cracker by incorporating meat of kilka, an under utilised fishery resource of the Caspian sea. 17 formulae with varying amounts of ingredients were tried initially and a formula that was found to be the best was selected. The fish:flour ratio in the selected formula was optimised so that a product of maximum linear expansion, crispness and best organoleptic qualities was obtained. The cracker produced remained in acceptable condition for 4 months at room temperature.